Pengaruh Model Pembelajaran Berbasis Teknologi Terhadap Kemampuan Berpikir Kritis Siswa Pada Mata Pelajaran Akidah Akhlak di SMP Muhammadiyah 8 Surakarta Tahun Pelajaran 2024/2025 - Aisyah Az Zahra; Muhammad Jafar Nashir (At Turots: Jurnal Pendidikan Islam, 2025)
This study aims to: (1) identify the extent of the use of information technology-based learning media at Muhammadiyah 8 Junior High School Surakarta in the 2024/2025 academic year, (2) determine students’ critical thinking skills in the Akidah Akhlak subject, and (3) examine the influence of technology-based learning models on students’ critical thinking skills. The research employed a quantitative correlational method with a population of 30 students from class IT 1. Data collection techniques included observation, questionnaires, and documentation. Data analysis used the Pearson Product Moment correlation test.The findings reveal that: (1) the implementation of technology-based learning is categorized as "moderate," with 15 students (51.73%) falling into this category; (2) students’ critical thinking skills are also categorized as "moderate," with 16 students (53.33%) in this range; and (3) there is a moderately strong correlation between the use of technology-based learning models (variable X) and students’ critical thinking skills (variable Y), with a correlation coefficient of 0.561 and a significance level of 0.001 (< 0.05). Regression analysis indicates that the technology-based learning model contributes 31.5% to the development of students' critical thinking skills, while the remaining 68.5% is influenced by other factors. The Adjusted R Square value of 0.291 and a standard error of estimate of 6.586 suggest that the regression model has an acceptable level of accuracy.